1993
DOI: 10.1039/an9931801425
|View full text |Cite
|
Sign up to set email alerts
|

L-Cysteine as a reducing and releasing agent for the determination of antimony and arsenic using flow injection hydride generation atomic absorption spectrometry—Part 2. Interference studies and the analysis of copper and steel

Abstract: A method was developed for the determination of antimony and arsenic in copper and steel using f l o w injection hydride generation atomic absorption spectrometry (FI-HGAAS) and L-cysteine as reducing and releasing agent. Tolerance limits (less than 10% interference) of at least 250 and 500 m g 1-1 were found for nickel and copper, respectively, in the presence of 1 % m/v L-cysteine, in the determination of antimony. For the determination of arsenic the corresponding tolerance limits were 200 mg 1-1 for nickel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…for As [18,20,22], for Sb [17,18,22], and for Bi [1], with 1% L-cysteine added in this work. L-cysteine was preferred because of the reasons given in the introduction and the tested conditions are summarized in Table 1.…”
Section: Hydride Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…for As [18,20,22], for Sb [17,18,22], and for Bi [1], with 1% L-cysteine added in this work. L-cysteine was preferred because of the reasons given in the introduction and the tested conditions are summarized in Table 1.…”
Section: Hydride Generationmentioning
confidence: 99%
“…The addition of L-cysteine to the sample solutions permits full recovery of the As signals [16,18,19] and of the Sb response [18,19] in presence of transition metals which interfere in the hydride generation step. In the presence of L-cysteine the pentavalent states of As and Sb are reduced and the trivalent state stabilized [18][19][20][21][22], thus making a separate reducing step obsolete. As and Sb hydride production by flow-injection in presence of 1% L-cysteine reached optimum conditions at low acid concentrations, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the masking agent used might also improve 1.0% m/v Flow rate of solutions 0.80 mL min À1 Length of mixing coil 1 10 cm Length of mixing coil 2 10 cm the hydride generation efficiency of some elements. In this work, citric acid (Chen, Zhu, & Wu, 1994), L-cysteine (Chen, Brindle, & Le, 1992;Welz & Sucmanová, 1993), tartaric acid (Chen & Jiang, 2009b) and oxalic acid (Chen & Jiang, 2009b) were tested as masking agents to improve signals of As, Hg and Pb. From the experiments it was found that the addition of 1% m/v citric acid improved the ion signals of As and Hg and hence citric acid was selected as masking agent in this study.…”
Section: Selection Of Vapor Generation Conditionsmentioning
confidence: 99%
“…It is virtually nontoxic, fully effective even in acid concentrations up to 1 mol L 21 , and its solutions are stable for several weeks. Welz and Sucmanova (1993) believe that L-cysteine acted by protecting Sb from the interference of copper species deposited on the tubing of the FIA system they used. On the other hand, showed that L-cysteine is completely ineffective if stibine is electrochemically generated.…”
Section: Hydride Generation Atomic Absorption Spectrometry (Hgaas)mentioning
confidence: 99%